Influence of Adhesion Layers on the Surface Morphology of Platinum-based Bottom Electrodes for Pb(Zr,Ti)O3 Thin Films - Huy, Nguyen Thanh; Hung, Vu Ngoc (Communications in Physics, 2010)
A thin adhesion layer is required to glue Pt bottom electrodes of ferroelectric Pb(Zr,Ti)O3 thin films to a SiO2/Si wafer. Here we report the effect of adhesion layers, Ti and TiO2, on the crystalline structure and surface properties of Pt electrode. The results show the hillock formation is observed for the case of Ti glue layer, while the surface of Pt layer is flat and uniform with TiO2 layer used instead. The crystallization in PZT thin films on Pt/TiO2/SiO3/Si substrate is investigated during post-deposition annealing. The perovskite phase is completely formed in the film annealed at 650oC for one hour.